2008
DOI: 10.1016/j.neuropharm.2008.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D1 vs D5 receptor-dependent induction of seizures in relation to DARPP-32, ERK1/2 and GluR1-AMPA signalling

Abstract: SummaryRecent reports have shown that the selective dopamine D 1 -like agonist SKF 83822 [which stimulates adenylate cyclase, but not phospholipase C] induces prominent behavioral seizures in mice, whereas its benzazepine congener SKF 83959 [which stimulates phospholipase C, but not adenylate cyclase] does not. To investigate the relative involvement of D 1 vs D 5 receptors in mediating seizures, ethological behavioral topography and cortical EEGs were recorded in D 1 , D 5 and DARPP-32 knockout mice in respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 51 publications
0
42
0
1
Order By: Relevance
“…An alternative interpretation of the lack of effect of SKF 83959 on extinction is based on work identifying SKF 83822 as a protein kinase A (PKA)-coupled D1/5 receptor agonist and SKF 83959 as a phospholipase C (PLC)-coupled D1/5 receptor agonist (O'Sullivan et al, 2008;Beaulieu et al, 2015). According to this interpretation, activating PKA-coupled, but not PLC-coupled D1/5 receptors can enhance fear extinction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative interpretation of the lack of effect of SKF 83959 on extinction is based on work identifying SKF 83822 as a protein kinase A (PKA)-coupled D1/5 receptor agonist and SKF 83959 as a phospholipase C (PLC)-coupled D1/5 receptor agonist (O'Sullivan et al, 2008;Beaulieu et al, 2015). According to this interpretation, activating PKA-coupled, but not PLC-coupled D1/5 receptors can enhance fear extinction.…”
Section: Discussionmentioning
confidence: 99%
“…SKF 83822 and SKF 83959 (Tocris) were dissolved in 10% DMSO (dimethyl sulfoxide in distilled water) and administered subcutaneously. Drug dosing for SKF 83822 (0.1, 1, 2 mg/kg) and SKF 83959 (0.1, 1, 10 mg/kg) were estimated based on doses used by O'Sullivan et al (2008).…”
Section: Drugsmentioning
confidence: 99%
“…Initially, the majority of results on D 1 -like receptor agonist effects on behavioral seizure thresholds clearly indicated proconvulsant effects (Starr, 1996). Nevertheless, recent reports showed that D 1 -like receptor agonists, linked to stimulation of adenylate cyclase (AC; but not phospholipase C, PLC), led to prominent behavioral seizures in rodents, whereas D 1 -like receptor agonists, linked to stimulation of phospholipase C (PLC, but not AC), did not (O'Sullivan et al, 2008). The D 5 R belongs to the D 1 -like receptor family and upon its activation mainly increased excitation is observed, although less prominent in comparison with D 1 R activation and subsequent increases in cAMP (O'Sullivan et al, 2008).…”
Section: Monoamines In Epilepsy: Preclinical and Clinical Evidencementioning
confidence: 99%
“…In addition, several reports highlight that modulation of D1Rs could impact on the seizure threshold. Indeed, the administration of D1R-like agonist induces seizures (Gangarossa et al, 2011;O'Sullivan et al, 2008) and decrease seizure threshold in the pilocarpine model (al-Tajir et al, 1990;Alam and Starr, 1992). Moreover, D1R neuron-ablated mice displayed spontaneous stereotyped seizures, which have been associated to cell loss, astrogliosis and microgliosis in the dentate gyrus (Gantois et al, 2007).…”
Section: Introductionmentioning
confidence: 99%